AMELIORATION OF GENOTOXICITY BY PAPAYA EXTRACT INDUCED BY ARSENIC CONTAMINATED DRINKING WATER - NEHA SINGH, DHARMSHILA KUMARI (The Bioscan, 2013)
Arsenic is an established genotoxic carcinogen in human. Arsenic trioxide (0.04mg/animal) when administered orally daily to albino swiss mice for 15 continuous days, increased the incidence of abnormalities to 30.6% in meiotic metaphase chromosome, 5.88% in the gross morphology of sperm head and decreased the sperm count per unit volume of caput epididymal suspension to 64.16 in comparison to the control. The concurrent treatment of papaya fruit extract and arsenic trioxide significantly decreased the abnormalities to19.6% in meiotic chromosome, 4.16% in the sperm head morphology and increased the mean count of sperm to 82.28. The increase in abnormality of meiotic chromosome as well as abnormality in gross morphology of the sperm head and decrease in sperm count, as observed upon arsenic trioxide treatment, were ameliorated by the aqueous papaya fruit extract. Therefore, it is suggested that the papaya fruit extract may reduce the risk of arsenic-induced genotoxicity.